Evolve the Controller for Static Synchronous Series Compensator Based on Control Strategy of Sen Transformer - Raju Jayaraman; Kowslaya M (International Journal of Power Electronics and Drive Systems (IJPEDS), 2014)
Real and Reactive power flow in an alternating current transmission line can be independently controlled by connecting, to the transmission line, a series-compensating voltage, which is variable in magnitude and phase angle. The Static Synchronous Series Compensator (SSSC), a solid-state voltage source inverter (VSC) coupled with a transformer, is connected in series with a transmission line. An SSSC injects an almost sinusoidal voltage, of variable magnitude, in series with a transmission line. This injected voltage is almost in quadrature with the line current, thereby emulating an inductive or a capacitive reactance in series with the transmission line. This emulated variable reactance, inserted by the injected voltage source, influences the electric power flow in the transmission line. In this report, an attempt is made to evolve the model of SSSC and VSC with preliminary studies for the controller design.DOI: http://dx.doi.org/10.11591/ijpeds.v4i1.5246